Clinical and economic burden of Richter syndrome in inpatient cases of chronic lymphocytic leukemia within the United States, 2001–2010. Issue 4 (April 2014) - Skrepnek, Grant H.; Tate, Wendy R.; Baker, Amanda F.
Abstract Richter syndrome (RS) is an aggressive transformation of chronic lymphocytic leukemia (CLL) characterized by poor prognoses. The purpose of this study was to assess clinical and economic characteristics of RS within inpatient hospital settings in the United States from 2001 to 2010. This retrospective cohort study employed data from the Agency for Healthcare Research and Quality's Healthcare Cost and Utilization Project. Overall, 46 613 cases of RS were observed across 695 080 inpatient cases of CLL, representing a national bill of $2.74 billion and involving a 9.3% inpatient mortality rate. Multivariate analyses found decreased national inpatient mortality from 2001 to 2010 of − 61.1% (p < 0.001), shorter length of stay of − 15.5% (p < 0.001) and higher charges of +20.9% (p = 0.003). Numerous characteristics were also associated with increased likelihoods of death, lengths of stay and charges. Clinically, the findings allow for an increased understanding of population-based RS case-mixes, outcome prediction and clinical risk assessments. The continued burden of illness of either RS or CLL ultimately remains contingent upon the comparative- and cost-effectiveness of both existing interventions and those in development.